2022
DOI: 10.3390/bioengineering9100574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lower Extremity Joint Moment and Power Estimated by Markerless and Marker-Based Systems during Treadmill Running

Abstract: Background: Markerless (ML) motion capture systems have recently become available for biomechanics applications. Evidence has indicated the potential feasibility of using an ML system to analyze lower extremity kinematics. However, no research has examined ML systems’ estimation of the lower extremity joint moments and powers. This study aimed to compare lower extremity joint moments and powers estimated by marker-based (MB) and ML motion capture systems. Methods: Sixteen volunteers ran on a treadmill for 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…Joint position differences between marker-based and markerless concurrent data were found to be 3 cm or smaller for all joints, which is consistent with previous comparisons of these systems during treadmill walking (Kanko et al, 2021a). Joint position component differences were also mostly consistent with those of Tang et al, however they did not report 3D Euclidean distances (Tang et al, 2022).…”
Section: Alternative Marker-based Modelling Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Joint position differences between marker-based and markerless concurrent data were found to be 3 cm or smaller for all joints, which is consistent with previous comparisons of these systems during treadmill walking (Kanko et al, 2021a). Joint position component differences were also mostly consistent with those of Tang et al, however they did not report 3D Euclidean distances (Tang et al, 2022).…”
Section: Alternative Marker-based Modelling Resultssupporting
confidence: 89%
“…Segment and joint angles demonstrated similar agreement between motion capture systems as in our previous study for treadmill walking gait (Kanko et al, 2021a), and excellent agreement across asynchronous markerless clothing conditions. Sagittal plane joint angles between motion capture systems had mean RMSD of 5.2° or less for all three joints, consistent with the findings of Tang et al (Tang et al, 2022). The differences between systems measured as mean RMSD over the entire gait cycle are comparable to reported minimal detectable change (MDC) values for marker-based motion capture of treadmill running at initial contact (Bramah et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the fidelity of markerless motion capture in quantifying 3D joint kinematics and kinetics has not been fully verified against standard marker-based techniques. To our knowledge, only three recent studies compared lower extremity 3D kinematics or kinetics from concurrent marker-based and markerless motion capture (Ito et al, 2022; Kanko et al, 2021a; Tang et al, 2022). Kanko et al (2021a) found comparable kinematics between the two systems during treadmill walking.…”
Section: Introductionmentioning
confidence: 99%